Ethical challenges in primary care: a focus group study with general practitioners, nurses and informal caregivers - Gagyor, Ildik; Hessling, Arndt; Heim, Susanne; Frewer, Andreas; Nauck, Friedemann; Himmel, Wolfgang (Family Practice, 2019)
General practitioners (GPs), nurses and informal caregivers are often jointly involved in healthcare situations in which ethical issues play an important role.
CRIS-Team WoS Importer:2019-04-12